Understanding the Determinants of Decision Making Among Online Food Delivery App Users in Can Tho City, Vietnam - Hong Tran, Kiet; Nguyen, Kim Van; Thyen Ly, Thoa (PT. Sangadji Media Publishing, 2024)
This research explores the determinants influencing decision making among online food delivery app users in Can Tho City, Vietnam, against the backdrop of the city's evolving culinary landscape and the rapid expansion of digital technologies. Through qualitative methods including semi-structured interviews, thematic analysis, participant observation, and document analysis, key factors driving user decisions are identified. These factors include convenience, trust, food quality, delivery time, price sensitivity, and social influences. The findings underscore the complexity of user behavior within this context and highlight the importance of addressing these factors to improve user satisfaction and engagement with online food delivery apps. Despite the study's valuable insights, limitations such as geographical specificity, sample size, and reliance on self-reported data are acknowledged, suggesting avenues for future research including longitudinal studies, comparative analyses, experimental interventions, and quantitative assessments. By addressing these gaps, future research can advance our understanding of user behavior in online food delivery contexts and inform strategies for enhancing the user experience.